Решите уравнение :(х-3)(хВ КВАДРАТЕ+3Х+9)-Х(Х В КВАД-16)=21, 16Х(4Х В КВ-5)+17=(4Х+1)(16Х В КВ -4Х+1)

1

Ответы и объяснения

2013-01-11T19:28:24+04:00

(x-3)*(x^2+3*x+9)-x*(x^2-16) = 21

(x-3)*(x^2+3x+9)-x*(x^2-16)=16x-27 (преобразование для левой части уравнения)

16x-27=3*7

16x-27=21

16x=48(16 удаляем)

x=3

___________________________________________

16Х(4Х^2-5)+17=(4Х+1)(16Х^2-4Х+1)

16x*(4x^2-5)+17=64x^3-80x+17

64x^3-80x+17=(4x+1)(16x^2-4x+1)

x=1/5

___________________________________________

Где "^" - степень